PENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM MELALUI MEDIA VIDEO PADA SISWA KELAS V - Tri Marleni (Universitas Sebelas Maret, 2022)
During the COVID-19 period of online learning, it was found that class V students at SD Negeri 1 Mlese found that the implementation of active and effective learning had not yet become a culture of being applied in distance learning. Learning is expected to attract children's interest to pay more attention to learning, train students' concentration and imagination. The research method used is descriptive qualitative. Researchers identified problems directly to schools to obtain data on student learning outcomes in grade 5 Natural Sciences subjects. Learning media are educational tools that can be used as intermediaries in the learning process to increase effectiveness and efficiency and teaching objectives (Hujair, 2009: 4) . Based on the background stated above, the aim of this research is an effort to improve science learning outcomes through video learning media for class V students at SD Negeri 1 Mlese.